CHARACTERIZATION OF CONSULTATIONS REQUESTED FOR PATIENTS WITH ELEVATED BLOOD EOSINOPHILS: A TERTIARY IMMUNOLOGY AND ALLERGY CLINIC EXPERIENCE - Şengül Beyaz; Zeynep Çelebi Sözener; Şadan Soyyiğit (İstanbul Tıp Fakültesi Dergisi)
Objective: Blood eosinophilia has become a common laboratory abnormality and its characterization poses a dilemma for physicians. As a result, physicians often consult specialists in immunology and allergy in order to evaluate patients with high eosinophils, with the general assumption of an underlying allergic or immunologic cause. However, there is little data in the literature regarding consultations requested from immunology and allergy clinics because of eosinophilia. This study aimed to evaluate the clinical and demographic characteristics of patients who were consulted to the allergy clinic because of eosinophilia and detail the etiologies of eosinophilia. Methods: The medical records of 1366 patients consulted to the allergy clinic were evaluated retrospectively, and the data of 143 patients who were consulted for eosinophilia were investigated. Results: The median (range) eosinophil count was 2456 cells/ mm3 (520-42920). 86 (60.1%) patients were classified as mild (500 to 1500 cells/mm3 ), 44 (30.8%) patients as moderate (1500 to 5000 cells/mm3 ), and 13 (9.1%) patients as severe (≥5000 cells/ mm3 ) eosinophilia. The most frequently consulted departments were chest diseases (37.1%), internal medicine (34.2%), and dermatology (14.7%), respectively. While the most common clinical symptoms at presentation were cough, dyspnea, pruritus, rhinitis, and gastrointestinal symptoms, 49 (34.3%) patients were asymptomatic. The mean±SD vitamin B12 and tryptase levels were 424.2±240.5 pg/mL, and 4.48±1.76 ng/mL, respectively. The median total IgE level was 150 IU/mL (1.5-9464). Atopy wasidentified in 26.6% (n=38) of the patients. Among 143 eosinophilia patients, there were no patients diagnosed with myeloproliferative or lymphocytic variants of hypereosinophilic syndrome (HES), eight patients were diagnosed with idiopathic HES. While the most common underlying causes were asthma (n=38) and allergic rhinitis (n=20), 30 patients had non-allergic causes. Conclusion: Although parasitic infections and allergic diseases are the first etiologies that come to mind when eosinophilia is detected in a patient, a specific anamnesis and advanced diagnostic tests for differential should be performed in order to detect other underlying or accompanying conditions apart from these diseases.